Cumulative impact of swimmers on pool water quality: A full-scale study revealing seasonal and daily variabilities of disinfection by-products. Issue 6 (December 2021) - Delpla, Ianis; Simard, Sabrina; Proulx, François; Sérodes, Jean-Baptiste; Valois, Isabelle; Ahmadpour, Elham; Debia, Maximilien; Tardif, Robert; Haddad, Sami; Rodriguez, Manuel
Abstract: Swimming pool water is continuously disinfected to control microbial safety. However, the disinfection processes also generate disinfection by-products (DBPs) that are created by the reaction between a disinfectant and organic matter. In this study, the water quality of two indoor pools with different characteristics was monitored at full scale. To assess the cumulative impact of swimmers, pools water quality was monitored for long term (2 months), after complete water renewal in pools. The daily impact of swimmers on water quality was also estimated by intensively sampling water quality during one high attendance day. Samples were analyzed for DBPs (Trihalomethanes-THMs, Haloacetic acids-HAAs, chlorites and chlorates) and their precursors (total organic carbon-TOC, UV 254 nm, water temperature, pH, free and total chlorine). Results showed that swimmers had a clear impact on the levels of organic matter indicators (TOC and UV 254 nm) and total nitrogen, whose variabilities were associated with the swimmers attendance. The highest levels of DBPs (THMs and HAAs) were detected in the pools during periods of maximum attendance and when there was a higher ratio of swimmers to pool-water volume. THM levels were also found to be influenced by parameters associated with pool operations (water temperature, water renewal, disinfection). Most notably HAAs accumulated in both pools due to their low volatility. Further studies should include nitrogenous DBPs, given their important toxicity, and should assess the impact of water quality and ventilation on the presence of volatile DBPs in air. Graphical Abstract: ga1 Highlights: Disinfection by-products (THM, HAA, chlorite, chlorate) were analyzed in pool water. Highest levels of DBPs in the pools were found in periods of maximum attendance. Considerable daily variability in THMs, HAAs and chlorate was found. Cumulative impact of swimmers on water quality throughout the season was observed.